To combine the radicals in the expression \( \sqrt{4396} + \sqrt{44} - \sqrt{2275} \), we first simplify each radical.
-
Simplify \( \sqrt{4396} \):
- Find the prime factorization of \( 4396 \).
- \( 4396 = 4 \times 1099 = 2^2 \times 1099 \).
- Thus, \( \sqrt{4396} = \sqrt{4 \times 1099} = \sqrt{4} \times \sqrt{1099} = 2\sqrt{1099} \).
-
Simplify \( \sqrt{44} \):
- \( 44 = 4 \times 11 \).
- Thus, \( \sqrt{44} = \sqrt{4 \times 11} = \sqrt{4} \times \sqrt{11} = 2\sqrt{11} \).
-
Simplify \( \sqrt{2275} \):
- Find the prime factorization of \( 2275 \).
- \( 2275 = 25 \times 91 = 5^2 \times 7 \times 13 \).
- Thus, \( \sqrt{2275} = \sqrt{25 \times 91} = \sqrt{25} \times \sqrt{91} = 5\sqrt{91} \).
Now substituting the simplified forms back into the original expression:
\[ 2\sqrt{1099} + 2\sqrt{11} - 5\sqrt{91} \]
Since \( \sqrt{1099} \), \( \sqrt{11} \), and \( \sqrt{91} \) are unlike radicals, they cannot be combined further.
Therefore, the expression in simplest radical form is:
\[ \boxed{2\sqrt{1099} + 2\sqrt{11} - 5\sqrt{91}} \]